Isolation and Identification of Bacterial Flora from Foot Lesions of Asian Elephants (Elephas maximus) - Veeraselvam, M.; Selvaraj , P.; Kumar , S. Senthil; Senthilkumar, A.; Senthilkumar , T.M.A.; Jayalakshmi , K.; Priya, R. Jyothi; Tamileniyan , E. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study was undertaken for the isolation and identification of the bacterial agents present in the foot lesions of captive elephants. A total of 78 samples were collected from various foot lesions of 46 captive elephants and subjected to bacterial culture. Sixteen of these collected samples did not show any bacterial growth in any type of media. The remaining 62 samples had 155 isolates; 94 (60.6%) of them were Gram negative bacteria, and the rest 61 (39.3%) isolates were Gram positive bacteria. Among the 155 isolates, they comprised of E. coli 63 (40.6%), Bacillus species 25 (16.1%), Pseudomonas species 18 (11.6%), 36 (23.2%), Staphylococcus species, Citrobacter species 3 (1.9%) and Enterobacter species 14 (9.03%). The study highlights the microbiological fauna of foot lesions, emphasizing the prevalence of Gram-negative bacteria and underscoring the need for periodic health screening and targeted interventions for captive elephants’ welfare.